Lack of muscle fibre hypertrophy, myonuclear addition, and satellite cell pool expansion with resistance training in 83‐94‐year‐old men and women. (20th March 2019) - Karlsen, Anders; Bechshøft, Rasmus L.; Malmgaard‐Clausen, Nikolaj M.; Andersen, Jesper L.; Schjerling, Peter; Kjaer, Michael; Mackey, Abigail L.
Abstract: Aims: To examine satellite cell and myonuclear content in very old (≥83 years) individuals, and the response to heavy resistance training. Methods: A group of very old men and women (Old, 83‐94 years, n = 29) was randomized to 12 weeks of heavy resistance training or untrained controls. A group of young men who did not resistance train (Young, 19‐27 years, n = 9) were included for comparison. Results: Compared to young men, prior to training the old men had smaller type II fibres (−38%, P  < 0.001), lower satellite cell content (−52%, P  < 0.001), smaller myonuclear domain (−30%, P  < 0.001), and a trend for lower myonuclear content (−13%, P  = 0.09). Old women were significantly different from old men for these parameters, except for satellite cell content. Resistance training had no effect on these parameters in these old men and women. Fibre‐size specific analysis showed strong correlations between fibre size and myonuclei per fibre and between fibre size and myonuclear domain for both fibre types ( r  = 0.94‐0.99, P  < 0.0001). In contrast, muscle fibre perimeter per myonucleus seemed to be constant across the range in fibre size, particularly in type I fibres ( r  = −0.31, P  = 0.17). Conclusions: The present data demonstrate that type II fibre size, satellite cell content and myonuclear domain is significantly smaller in very old men compared to young men, while myonuclear content is less affected. These parameters were not improved with heavy resistance training at the most advanced stage of ageing.